Changing agrarian structure in Bangladesh Shimulia, a study of a periurban village - Arefeen, Helaluddin K. S. (Dhaka : Centre for Social Studies : Distributor, Dana Publishers, 1986)
Study of a village near Dhaka City; covers the period, 1945-1978.
Revision of the author's thesis (Ph. D.--Syracuse University, 1983)
Master microform held by: DLC.
Bibliography: p. 164-171.
Microfiche.